2012
DOI: 10.1089/scd.2011.0030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Differentiation Potential of Murine Mesenchymal Stem Cells from Tissues of Endodermal or Mesodermal Origin

Abstract: Mesenchymal stem cells (MSCs) have received great attention due to their remarkable regenerative, angiogenic, antiapoptotic, and immunosuppressive properties. Although conventionally isolated from the bone marrow, they are known to exist in all tissues and organs, raising the question on whether they are identical cell populations or have important differences at the molecular level. To better understand the relationship between MSCs residing in different tissues, we analyzed the expression of genes related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…In contrast, genes that were minimally expressed in cardiac fibroblasts were induced in a specific temporal manner during the course of osteogenic differentiation (Figure 1C) and included sets of genes known to regulate inflammation, extracellular matrix proteins and cell metabolism (Figure S1A). Next, we created an osteogenic signature based on a set of 37 genes that are induced during osteogenic differentiation (Chen et al, 2012);(Choi et al, 2010);(Graneli et al, 2014);(Harkness et al, 2011);(Hoshiba et al, 2009);(Liu et al, 2013);(Miguez et al, 2014);(Nora et al, 2012);(Olivares-Navarrete et al, 2011) (Figure S1B). We used the mean fold change in expression of this set of genes to quantitatively determine an osteogenic signature and observed that compared to control cardiac fibroblasts, cardiac fibroblasts subjected to osteogenic differentiation progressively adopted an osteogenic signature (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, genes that were minimally expressed in cardiac fibroblasts were induced in a specific temporal manner during the course of osteogenic differentiation (Figure 1C) and included sets of genes known to regulate inflammation, extracellular matrix proteins and cell metabolism (Figure S1A). Next, we created an osteogenic signature based on a set of 37 genes that are induced during osteogenic differentiation (Chen et al, 2012);(Choi et al, 2010);(Graneli et al, 2014);(Harkness et al, 2011);(Hoshiba et al, 2009);(Liu et al, 2013);(Miguez et al, 2014);(Nora et al, 2012);(Olivares-Navarrete et al, 2011) (Figure S1B). We used the mean fold change in expression of this set of genes to quantitatively determine an osteogenic signature and observed that compared to control cardiac fibroblasts, cardiac fibroblasts subjected to osteogenic differentiation progressively adopted an osteogenic signature (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…1685 genes with a FDR < 0.05 and a minimum 2 fold (log 2 ) change were subsequently clustered and visualized. A set of osteogenic genes known to be induced during bone formation or osteogenic differentiation was compiled from the literature to determine an osteogenic signature (Chen et al, 2012); (Choi et al, 2010); (Graneli et al, 2014); (Harkness et al, 2011); (Hoshiba et al, 2009); (Liu et al, 2013); (Miguez et al, 2014); (Nora et al, 2012); (Olivares-Navarrete et al, 2011). All RNA-seq analysis were performed with ≥ 2 biological replicates.…”
Section: Methods Detailsmentioning
confidence: 99%
“…gene expression changes during in vitro differentiation to osteogenic, chondrogenic or adipogenic lineages [30]; [31], ii.) comparative analysis of bone marrow and adipose tissue-derived mesenchymal stromal cells in in vitro adipogenic, chondrogenic or osteogenic differentiation [32]; [33], and iii.)…”
Section: Discussionmentioning
confidence: 99%
“…These studies have found that stromal cells produced from these various cell and tissue types have a similar phenotype [28-32]. All express CD44, CD73, CD90 and CD105, but do not express hematopoietic cell markers.…”
Section: Discussionmentioning
confidence: 99%